2002
DOI: 10.1097/00042560-200206010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Computed Tomography for Assessment of Coronary Artery Disease in HIV-Infected Men Receiving Antiretroviral Therapy

Abstract: Hyperlipidemia has been seen in patients receiving protease inhibitor-based antiretroviral therapy, prompting concern that such patients are at risk for accelerated coronary artery disease (CAD). To assess the risk of CAD in antiretroviral-treated HIV-infected men, we quantified coronary artery calcium (CAC), a sensitive and established marker of subclinical CAD, using electron beam computed tomography (EBCT) of coronary vessels. Sixty HIV-infected men who met the following criteria (cases) were enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…Five studies reported incidence of CAC among HIV positive versus HIV negative patients 8 18 20 28 30. The pooled odds ratio for raised CAC by cardiac CT was not significant comparing HIV positive with HIV negative patients: OR = 0.95 (95% CI 0.55 to 1.65, p = 0.851); I2 = 65%, p = 0.024.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Five studies reported incidence of CAC among HIV positive versus HIV negative patients 8 18 20 28 30. The pooled odds ratio for raised CAC by cardiac CT was not significant comparing HIV positive with HIV negative patients: OR = 0.95 (95% CI 0.55 to 1.65, p = 0.851); I2 = 65%, p = 0.024.…”
Section: Resultsmentioning
confidence: 95%
“…Of 58 articles selected for detailed evaluation, 13 were excluded owing to missing data or comparison groups not relevant to our study question, 20 were duplicate data and 25 were included from the initial search 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32. After the addition of a study identified from the references of included articles a total of 26 articles were included 33.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in agreement with the literature, where similar numbers were found when adjusted for the age of the patients studied (mean, 43.4 years) 10 . Talwani et al 11 had previously reported that the calcium score in the HIVpositive population on antiretroviral therapy for at least 6 months was not significantly different from that of persons not carrying the virus. Kingsley et al 10 found a positive calcium score in 12% of patients under 45 years of age and HIV positive and in 23% of patients aged 40-45 years.…”
Section: Discussionmentioning
confidence: 97%